(untitled) (Margalla Papers, 2023)
The recent Pulwama incident has further strained the already tense relationship between India and Pakistan. India's violation of the UN resolution on Kashmir has exacerbated the situation, leaving both countries with seemingly no common ground or shared challenges to bring them to the dialogue table and build confidence and trust for a sustainable relationship. This paper proposes a peace-initiating process prioritising cooperation on common environmental challenges to improve bilateral relations between Pakistan and India. Environmental peacebuilding, which focuses on shared ecological challenges and provides a platform for dialogue and cooperation between rival states, has been explored for a couple of years. However, the cooperative dimensions of environmental peacebuilding have yet to be studied in bilateral relations between Pakistan and India. This paper provides a brief qualitative analysis of relations between two countries, highlights the potential for environmental peacebuilding to improve their relationship, and addresses challenges to successfully implementing this approach. Bibliography Entry Khan, Omair Farooq. 2023. "Pakistan-India Bilateral Relations and Application of Environmental Peacebuilding." Margalla Papers 27 (1): 155-165.